Concurrent Cognitive Task Alters Postural Control Performance of Young Adults With Unilateral Cochlear Implants. - Orhan, Emre; Batuk, İsa Tuncay; Batuk, Merve Ozbal (Journal of Speech, Language & Hearing Research, 2025)
Purpose: The aim of this study was to investigate the balance performances of young adults with unilateral cochlear implants (CIs) in a dual-task condition. Method: Fifteen young adults with unilateral CIs and 15 healthy individuals were included in the study. The balance task was applied using the Sensory Organization Test via Computerized Dynamic Posturography. The Backward Digit Recall task was applied as an additional concurrent cognitive task. In the balance task, participants completed four different conditions, which gradually became more difficult: Condition 1: fixed platform, eyes open; Condition 3: fixed platform, eyes open and visual environment sway; Condition 4: platform sway, eyes open; Condition 6: platform sway, eyes open and visual environment sway. To evaluate the dual-task condition performance, participants were given cognitive and motor tasks simultaneously. Results: Visual (p = .016), vestibular (p < .001), and composite balance scores (p < .001) of CI users were statistically significantly lower than the control group. Condition 3 (p = .003), Condition 4 (p = .007), and Condition 6 (p < .001) balance scores of CI users in the single-task condition were statistically significantly lower than controls. Condition 6 (p < .001) balance scores of CI users in the dual-task condition were statistically significantly lower than the control group. Condition 1 score (p = .002) of the CI users in the dual-task condition showed a statistically significant decrease compared to the balance score in the single-task condition, while the Condition 6 score (p = .011) in the dual-task condition was statistically significantly higher than the balance score in the single-task cond ition. Conclusions: The balance performance of individuals with CIs in the dual-task condition was worse than typical healthy individuals. It can be suggested that dual-task performances should be included in the vestibular rehabilitation process in CI users in the implantation process in terms of balance abilities in multitasking conditions and risk of falling.